How is language knowledge related to verbal working memory among preschool children? Evidence from bilinguals and monolinguals - Anahita Shokrkon; Elena Nicoladis; Farzaneh Anjomshoae (Language Development Research, 2025)
The typical language development in bilingual children, which shows some similarities with atypical language development in monolinguals, displays unique characteristics when compared to monolingual counterparts. In order for clinicians to correctly diagnose bilingual children with atypical language development, it is important to have access to diagnostic tools that distinguish typical from atypical development. Measures of children’s verbal working memory, such as digit span and nonword repetition, may be just such diagnostic tools. However, some previous studies have suggested that measures of verbal working memory could be related to language-specific knowledge, such as vocabulary. The purpose of the present study was to test whether bilingual children’s performance on two verbal working memory tasks were related to their within-language vocabulary scores. Forty French-English bilingual preschoolers and 40 age-matched English monolingual children were administered a standardized vocabulary test in English, a nonword repetition task (NWR), and digit span tasks (both forward and backward). The results showed that the bilingual children scored significantly lower than the monolingual children on the vocabulary test, but not on the nonword repetition task nor on the digit span tasks. Moreover, vocabulary scores were not correlated with the verbal working memory tasks for monolingual children. For bilingual children the NWR was not correlated with vocabulary. NWR seems to be relatively free of language-specific knowledge, at least within this age group. We discuss the clinical implications of these results.